2017
DOI: 10.24200/jonus.vol2iss1pp177-193
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook for English Language Learning: The Differences Among Gender and Ethnicity

Abstract: This study investigates university students’ perceptions of using Facebook for English language learning based on gender and ethnicity. A survey was used for data collection, in which all 622 participants reported to having at least one Facebook account which they frequently accessed multiple times a day. The findings show that the students possessed positive attitudes, motivation, self-confidence in using Facebook to learn English language. They also reported to have acquired new English words and sentence st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…For example, Kabilan et al (2010) in their study found that students perceive the use of Facebook as an online language learning environment contributes towards improvements of their language skills as it facilitated practise of communication, writing, and reading skills as well as learning of new words. Kasuma (2017) in her study found use of Facebook for English language learning contributing towards her students' language acquisition in that it helped them learn new words and vocabulary. Her students also reported feeling more confident and motivated to read and communicate in English.…”
Section: Perceived Helpfulness Of Sns To Help Improve English Languagmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Kabilan et al (2010) in their study found that students perceive the use of Facebook as an online language learning environment contributes towards improvements of their language skills as it facilitated practise of communication, writing, and reading skills as well as learning of new words. Kasuma (2017) in her study found use of Facebook for English language learning contributing towards her students' language acquisition in that it helped them learn new words and vocabulary. Her students also reported feeling more confident and motivated to read and communicate in English.…”
Section: Perceived Helpfulness Of Sns To Help Improve English Languagmentioning
confidence: 97%
“…The same interest too can be seen among language educators and researchers in Malaysia as the number of research on SNSs especially Facebook and its use for language learning is on the rise (e.g. Kabilan, Ahmad & Abidin 2010;Looi & Yusop 2011;Yunus, Salehi & Chenzi 2012;Mahmud & Ching 2012;Kasuma 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Learners are also introduced to a variety range of discourse functions thus it improves language ability. This helped to spark creative distribution of language play, and also raise critical literacy (Kasuma, 2017).…”
Section: The Use Of Language On Social Mediamentioning
confidence: 99%
“…A study conducted by Bicen, Sadikoglu and Sadikoglu (2015) revealed that the utilization of social media has positive impacts on learning foreign language. However, a study done by Abbasova (2016) and Kasuma (2017) found that writing skill is negatively affected when using social media.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few research materials and discussions on business communities among various ethnic groups in Malaysia (Kasuma, 2017). This paper will examine the cross-ethnic relationships and social cohesion among the business community of different ethnic groups in Malaysia.…”
Section: Introductionmentioning
confidence: 99%